The Influence of Strategic Human Resources Management Practices Moderated by Job Engagement and Perceived Supervisor Support on Employee Retention - Tantry Yanuar Rahmat Syah; Gilang Ramadhan*; Rojuaniah Rojuaniah; Ikramina Larasati Hazrati Havidz; Teguh Aribowo (Riwayat: Educational Journal of History and Humanities, 2023)
This research was conducted to identify the effect of strategic human resources management practice (SHRMP) on employee retention in the property industry with the moderating effect of job engagement and perceived supervisor support. This study was designed using a purposive sampling method involving 158 respondents from the property industry. Data were analyzed using Structural Equation Model (SEM) with SmartPLS 3.0. Some of the findings in this study are that SHRMP has a direct effect on Employee Retention. Meanwhile, the moderating effect of Job Engagement and Perceived Supervisor Support has no significant effect on Employee Retention. The managerial implications of this research for industry practitioners and researchers are implementing SHRMP in companies by improving recruitment systems, establishing proper and ongoing training for employees, monitoring and evaluating performance appraisals, and adjusting compensation and benefits for the employees with high performance.